THERMOOXIDATIVE STABILITY OF JET FUEL WITH FULLERENES AS AN ADDITIVE - Іванов, С.В.; Єфименко, В.В.; Єфіменко, О.В. (Proceedings of National Aviation University, 2012)
Heating of fuels in presence of oxygen reduces their thermal-oxidative stability, leads to a solid phase in the form of sludge and tar, which, sedimented at the details of the fuel system, change its characteristics and cause contamination of fuel filters and injectors, spool control sticking, reduce efficiency of heat exchangers. Nanomaterials, performance of which is considerably superior to the natural materials, are the basis for the movement of humanity’s progress. Therefore, with a develpoment of technologies it has become necessary to carry out a research of modified additives – fullerens, to improve an oxidative stability of fuels. We have carried out an investigation of thermal-oxidative stability of fuel RT as a function of additive C60 concentration. The results has shown that even 0,043 g/l fullerene addition as an antioxidant, reduces the amount of sediment in the fuel almost by half. Usage of fullerenes for improvement of petroleum products performance properties is a promising area of research.